Hubungan Pemberian Susu Formula Dengan Kejadiaan Diare Pada Bayi Usia 0 – 6 Bulan - Irawan Anasta Putra (JAMBI MEDICAL JOURNAL "Jurnal Kedokteran dan Kesehatan", 2014)
ABSTRACT Background : Formula feeding in infants aged 0-6 months are very influential on the frequency of occurrence of diarrhea. Based on Indonesian Demographic and Health Survey (IDHS) 2002-2003 known that infants aged less than 4 and 6 months has been given milk other than breast feeding, each for by 12.8% and 8.4%. In Indonesia, diarrhea is one of the highest causes of mortality and morbidity on the child, especially under the age of 5 years. From Jambi City Health Department in 2012 known data is the incidence of diarrhea in children <1 year as much as 1403 people spread in 20 health centers. At the Puskesmas Kenali Besar in 2012, patients with diarrhea in children <1 year of 110 people. Methods : This study is using a survey research with cross sectional analytic. Subject of research is baby age of 0-6 months of which taken from urban village working area of Puskesmas Kenali Besar. The number of samples a total of 123 people. Data of this research was analyzed by test chi square. Results : From 123 sample of this research, there are 48 (39%) infants with granting milk formula and 75 (61.0%) infants with ASI exclusive. Infants who never diarrhœa a total of 78 people ( 63.4 % ) while infants who never experienced diarrhœa 45 people ( 36.6 % ). Based on the results of the test chi square obtained meaningful relations between the infants with granting milk formula with an occurrence diarrhœa in infants age 0-6 months in the working area Puskesmas Kenali Besar. Conclusion : An infant that is consuming milk formulæ risk having exposed diarrhœa of 6,250 times in infants who were given breast-fed exclusive Keywords : Diarrhea, Milk Formula